2020
DOI: 10.1002/ange.202004441
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activation of Amides and Hydrocarbons for Direct C(sp3)–H Acylation Enabled by Metallaphotoredox Catalysis

Abstract: The utilizations of omnipresent, thermodynamically stable amides and aliphatic C(sp3)−H bonds for various functionalizations are ongoing challenges in catalysis. In particular, the direct coupling between the two functional groups has not been realized. Here, we report the synergistic activation of the two challenging bonds, the amide C−N and unactivated aliphatic C(sp3)−H, via metallaphotoredox catalysis to directly acylate aliphatic C−H bonds utilizing amides as stable and readily accessible acyl surrogates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 87 publications
2
7
1
Order By: Relevance
“…Satisfactorily, this reaction also possessed a broad scope with respect to aryl iodides. Electron-poor (20,21), electron-neutral (22,23) and electron-rich aryl iodides (24, 25) were all found to be amenable substrates for effectively generating C-N cross-coupled products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfactorily, this reaction also possessed a broad scope with respect to aryl iodides. Electron-poor (20,21), electron-neutral (22,23) and electron-rich aryl iodides (24, 25) were all found to be amenable substrates for effectively generating C-N cross-coupled products.…”
Section: Resultsmentioning
confidence: 99%
“…4, we performed stoichiometric studies using presynthesized Ni(dtbbpy)ArI ( 56) and found that only a trace amount of the product was formed under light or in the dark. When TBPASbCl 6 was added as a single-electron oxidant to oxidize 56 to the corresponding Ni(III) species, 23 the yield of 3 could be increased significantly. These observations indicate that reductive elimination of the C-N bond proceeds not through an excited-state Ni(II) species but through a Ni(III) intermediate.…”
Section: Resultsmentioning
confidence: 99%
“…Other reports on functionalization of unactivated C-H bonds occurring in the presence of analogous metal/metal dual-catalytic systems further underscored the efficacy of the strategy. [56][57][58] Scheme 3. W-/Ni-catalyzed arylation of strong sp 3 -C-H bonds with aryl bromides enabled by light-driven hydrogen atom transfer (HAT) Cooperation between a photocatalyst (PC) and a hydrogen atom transfer (HAT) catalyst provided new opportunities for free radical organic chemistry.…”
Section: -Branched Aldehydesmentioning
confidence: 99%
“…Recent nickel/photoredox dualcatalyzed cross-coupling of acyl electrophiles with nucleophilic alkyl radical precursors have also been developed, but these reactions are also reluctant to tertiary coupling substrates. [40][41][42][43][44][45][46] Moreover, the coupling between tertiary acyl and tertiary alkyl fragments to synthesize exceptionally bulky 3 o -3 o dialkyl ketones remains the most challenging task in this area. Thus, further developing e cient methods for the construction of all carbon quaternary aliphatic ketones is highly desirable, given the importance of dialkyl ketones as versatile intermediates in organic synthesis and the prevalence of dialkyl ketones in nature products, pharmaceutical agents, and advanced materials.…”
Section: Introductionmentioning
confidence: 99%